Public Opinion and Expectations: Development of Public Health Education in China After COVID-19 Pandemic - Xin Shen; Crystal Jingru Li; Tianyi Dong; Hui Cao; Jing Feng; Zihui Lei; Zijian Wang; Xiaotong Han; Chuanzhu Lv; Chuanzhu Lv; Chuanzhu Lv; Yong Gan (Frontiers Media S.A., 2021)
Background: Policymakers must promote the development of public health education and human resources. As a feature of the political environment, public opinion is essential for policy-making, but virtually the attitudes of Chinese citizens toward human resources development in public health is unknown.Methods: This study conducted a crosssectional survey from February 4, 2021 to February 26, 2021 in China. We adopted a convenient sampling strategy to recruit participators. Participants filled out the questions, which assess the attitudes of the expanding public health professionals. A logistic regression analysis was given to identify the predictors associated with the attitudes of the subjects.Results: There were 2,361 residents who have finished our questionnaire. Chinese residents who lived in urban (OR = 1.293, 95% CI = 1.051-1.591), "themselves or relatives and friends have participated in relevant epidemic prevention work" (OR = 1.553, 95% CI = 1.160-2.079), "themselves or family members engaged in medical-related work" (OR = 1.468, 95% CI = 1.048-2.056), and those who "were aware of public health before the outbreak of COVID-19" (OR = 1.428, 95% CI = 1.125-1.812) were more likely to support the promotion of public health education and training.Conclusions: The present study found that 74.50% of Chinese citizens supported the promotion of public health education and training in China, in which economic status, personal perception, and comprehension are the crucial factors that influence public opinion. COVID-19 has aroused the attention of Chinese residents to public health education, with only 22.11% of residents being aware of public health before the outbreak of COVID-19. The COVID-19 pandemic has profound implications for human society. Literally, this impact will feed back into future public health policies based on public opinion. This innovative perspective will also help us better understand the potential social impact of COVID-19 on human resources and development for health in the modern world.